FRI0103 Vit d deficiency, depletion of circulating endothelial progenitor cells and impaired arterial stiffness in patients with ra. (23rd January 2014) - Lo Gullo, A.; Mandraffino, G.; Sardo, M. A.; Imbalzano, E.; Visalli, E.; Mamone, F.; Mandraffino, R.; Saitta, C.; Atteritano, M.; Lo Gullo, R.; Bagnato, G.; Saitta, A.
Abstract : Background: Vitamin D deficiency was recently acknowledged as an independent predictor of cardiovascular diseases and all-cause mortality in several clinical setting and its serum levels are commonly reduced in Rheumathoid Arthritis. (RA). Patients affected by RA present accelerated atherosclerosis and increased cardiovascular morbidity and mortality with respect to the general population. In RA an impairment of the number and the activity of circulating progenitor cells, including CD34+ cells and endothelial progenitor cells, appears to be involved in development of endothelial damage and cardiovascular diseases. Objectives: This study investigates the association between vitamin D deficiency and circulating progenitor cell number (CPCs). Methods: Circulating progenitor cells number and vitamin D levels were measured in 30 patients affected by RA and in 30 controls matched for age and gender. C-reactive protein (CRP), fibrinogen, erythrocyte sedimentation rate (ESR), carotid intima-media thickness (cIMT), augmentation index (AIx), pulse wave velocity (PWV) were also evaluated. We investigated the relationships among vitamin D and cell number, inflammatory markers, and vascular parameters. Results: In RA patients the levels of vitamin D were reduced with respect to controls (21.5±6.9 vs 37.6±13.2 ng/ml, p <0.001); CPCs number (1.80±0.59 vs 2.32± 0.34 cells/µL, p <0.001) was also significantly reduced. PWV and AIx were higher in RA, while cIMT was not different between RA patients and controls. Vitamin D correlate inversely with CPCs number and PWV (rs -0.49 p < 0.005 and rs -0.56, p< 0.001 respectively). In RA we identify no association between vitamin D and cIMT, CRP, ESR, fibrinogen. CPCs number correlates with CRP (rs -0.50, p<0.005) and ESR (rs= -0.57, p<0.001). Conclusions: Our findings suggest that Vitamin D deficiency is a common finding in RA and is associated with reduced CPCs counts. Future studies are needed to determine whether vitamin D supplementation could improve CPCs levels and arterial stiffness indices in patients affected by rheumathoid arthritis. References: Semba RD et al. Relationship of 25-hydroxyvitamin D with all-cause and cardiovascular disease mortality in older community-dwelling adults. Eur J Clin Nutr. 2010 Feb;64(2):203-9. Cutolo M at al. Vitamin D in rheumatoid arthritis. Autoimmun Rev. 2007 Nov;7(1):59-64. Haque UJ et al. Association of vitamin D with cardiometabolic risk factors in rheumatoid arthritis. ArthritisCare Res (Hoboken). 2012 Oct;64(10):1497-504. Herbrig K et al. Endothelial dysfunction in patients with rheumatoid arthritis is associated with a reduced number and impaired function of endothelial progenitor cells. Ann Rheum Dis 2006;65(2):157-63. Reynolds JA et al. 25-Hydroxyvitamin D deficiency is associated with increased aortic stiffness in patients with systemic lupus erythematosus. Rheumatology (Oxford). 2012 Mar;51(3):544-51. Disclosure of Interest: None Declared